A Frame for Multiculturalism Moderation in Perspective of Multiculturalism Education in Indonesia - Kurniawan, Kurniawan; Sureni, Sureni; Sa'diyah, Rika (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This article portrays religious moderation from the viewpoint of multicultural education in Indonesia. Religious moderation understanding and insight need to be developed to strengthen Indonesian society that distinction is not a disability but a gift from God as a plural form of nation and a requirement for culture. Through multiculturalism education by developing attitudes, norms, behavior, respecting differences, and cultural diversity (respecting other cultures) it is expected to preserve steadiness and concordance among citizens to coexist. The strategy utilized is library research. The article concluded that multiculturalism education in Indonesia can go well with a contextual and relevant understanding of religious moderation. In dealing with people with heterogeneous characters, a powerful medium is used through multiculturalism education to minimize radicalism in the form of knowledge, belief, or avoiding contradictory things that are incompatible with the tolerant nation's culture. This research aims to make Indonesia's diversity a valuable asset through multiculturalism education so that it can realize a diversity of national unity.